Human papillomavirus negative cervical cancers and precancerous lesions: prevalence, pathological and molecular features, and clinical implications - Liron Pantanowitz; Chengquan Zhao; Xianxu Zeng; Wenli Dai (Gynecology and Obstetrics Clinical Medicine)
Background: Cervical cancer is the fourth most common cancer in women globally. Although human papillomavirus (HPV) testing plays an increasing role in cervical cancer screening and treatment, HPV-negative cervical cancer remains a consistently reported entity globally. While numerous studies have focused on HPV-positive cervical cancers, detailed studies on HPV-negative counterparts remain limited.Results: This literature review aims to discuss several aspects of HPV-negative cervical cancers including the prevalence of HPV-negative cervical carcinomas and precancerous lesions and their relation to sample types (paraffin-embedded tissue blocks or liquid samples). Additionally, we explore possible reasons for false HPV-negative cases. Furthermore, we review histomorphological, molecular and clinical features of HPV-negative cervical cancers.Conclusions: The topic of HPV-negative cervical cancers is of importance given the drive towards HPV primary screening, initiation of self-collected HPV testing and widespread use of HPV vaccination.